Local-level People's Participation Intervention in Rethinking Architecture for Sustainable Societies - Nagpal, Aarti; Manchanda, Shweta (LPPM of NAROTAMA UNIVERSITY, 2025)
Sustainable societies rely on inclusive decision-making processes, where local-level people’s participation plays a critical role in shaping architecture and urban planning. This study explores how community engagement influences sustainable development at neighborhood and societal levels, particularly in India. Given the complexities of urbanization, cultural behavior, and governance, this research examines how participatory action can enhance sustainability efforts. Through a literature review and expert-level surveys, the study evaluates the impact of people’s behavior, decision-making, and participatory frameworks on architectural design and sustainable neighborhood planning. The findings indicate that participatory models, such as Participatory Action Research (PAR) and Sustainable Development Indicators (SDIs), can effectively integrate public engagement into sustainable assessment tools. Key sustainability aspects—including education, health, water conservation, waste management, and social cohesion—benefit from people’s participation. The research suggests that tools like GRIHA, LEED-ND, and IGBC for Green Residential Societies should incorporate participatory frameworks to enhance sustainability measurement and implementation. This study contributes to rethinking architecture and planning by linking local decision-making with sustainable urban development.